Constraints on Seismic Anisotropy in the Mantle Transition Zone From Long‐Period SS Precursors. Issue 7 (12th July 2019) - Huang, Quancheng; Schmerr, Nicholas; Waszek, Lauren; Beghein, Caroline
Abstract: The mantle transition zone (MTZ) of Earth is demarcated by solid‐to‐solid phase changes of the mineral olivine that produce seismic discontinuities at 410 and 660‐km depths. Mineral physics experiments predict that wadsleyite can have strong single‐crystal anisotropy at the pressure and temperature conditions of the MTZ. Thus, significant seismic anisotropy is possible in the upper MTZ where lattice‐preferred orientation of wadsleyite is produced by mantle flow. Here, we use a body wave method, SS precursors, to study the topography change and seismic anisotropy near the MTZ discontinuities. We stack the data to explore the azimuthal dependence of travel‐times and amplitudes of SS precursors and constrain the azimuthal anisotropy in the MTZ. Beneath the central Pacific, we find evidence for ~4% anisotropy with a SE fast direction in the upper mantle and no significant anisotropy in the MTZ. In subduction zones, we observe ~4% anisotropy with a trench‐parallel fast direction in the upper mantle and ~3% anisotropy with a trench‐perpendicular fast direction in the MTZ. The transition of fast directions indicates that the lattice‐preferred orientation of wadsleyite induced by MTZ flow is organized separately from the flow in the upper mantle. Global azimuthal stacking reveals ~1% azimuthal anisotropy in the upper mantle but negligible anisotropy (<1%) in the MTZ. Finally, we correct for the upper mantle and MTZ anisotropy structures to obtain a new MTZ topography model. The anisotropy correction produces ±3 km difference and therefore has minor overall effects on global MTZ topography. Key Points: The MTZ anisotropy is investigated from the SS precursors at both regional and global scales We observe ~3% anisotropy in the MTZ beneath subduction zones but negligible MTZ anisotropy (<1%) at a global scale We propose a new MTZ topography model corrected for the upper mantle and MTZ anisotropy structures